Leveraging digital tools to enhance diversity and inclusion in clinical trial recruitment - Tosin Tomiwa; Tosin Tomiwa; Erin Wong; Hailey N. Miller; Oluwabunmi Ogungbe; Samuel Byiringiro; Timothy Plante; Cheryl R. Himmelfarb; Cheryl R. Himmelfarb; Cheryl R. Himmelfarb (Frontiers in Public Health)
Clinical research is pivotal in assessing the safety and efficacy of new treatments in healthcare. However, the success of such research depends on the inclusion of a diverse and representative participant sample, which is currently lacking. This lack of diversity in biomedical research participants has significant repercussions, limiting the real-world applicability and accessibility of medical interventions, especially for underrepresented groups. Barriers to diverse participation include historical mistrust, logistical challenges, and financial constraints. Recent guidelines by government agencies and funding bodies emphasize the need for diversity in clinical trials, but specific strategies for inclusive recruitment are often lacking. This paper explores the use of digital methods to enhance diversity and inclusion in research recruitment. Digital tools, such as electronic medical records, social media, research registries, and mobile applications, offer promising opportunities for reaching diverse populations. Strategies include culturally tailored messaging, collaborations with community organizations, and the use of SEO to improve visibility and engagement. However, challenges such as privacy concerns, digital literacy gaps, and ethical considerations must be addressed. The promotion of diversity in clinical research recruitment is crucial for advancing health equity. By leveraging digital tools and adopting inclusive strategies, study teams can improve the diversity of study participants, ultimately leading to more applicable and equitable healthcare outcomes.